A Right-to-Health Lens on Perinatal Mental Health Care in South Africa - Shelley Brown; Gillian MacNaughton; Courtenay Sprague (Harvard FXB Center for Health and Human Rights, 2020)
South African women experience some of the highest rates of depression and anxiety globally. Despite South Africa's laudable human rights commitments to mental health in law, perinatal women are at high risk of common mental disorders due to socioeconomic factors, and they may lack access to mental health services. We used a right to mental health framework, paired with qualitative methods, to investigate barriers to accessing perinatal mental health care. Based on in-depth interviews with 14 key informants in South Africa, we found that (1) physical health was prioritized over mental health at the clinic level; (2) there were insufficient numbers of antenatal and mental health providers to ensure minimum essential levels of perinatal mental health services; (3) the implementation of human rights-based mental health policy has been inadequate; (4) the social determinants were absent from the clinic-level approach to mental health; and (5) a lack of context-specific provider training and support has undermined the quality of mental health promotion and care. We offer recommendations to address these barriers and improve approaches to perinatal mental health screening and care, guided by the following elements of the right to mental health: progressive realization; availability and accessibility; and acceptability and quality.